The Legal Adaptation of Internet Subscription Contracts -Analytical Study - Roshna Akram Saad (QALAAI ZANIST JOURNAL, 2020)
This research aims to clarify The Legal Adaptation of Internet Subscription Contracts that include a set of conditions prepared by the company providing Internet services and impose them on the subscriber without discussing them. Legislators and legal jurists have agreed to name the type of contract in which one party to the contract complies with the will and conditions of the other party without observing the counterparty’s desire to comply, with the Adhesion contract. In this research we reached that the internet subscription contract contains arbitrary conditions that relate to an exemption from liability or to reduce the company from its obligations or relate to increasing obligations and burdens on the subscribers or depriving them of some legal rights, and imposed by the strong party, the company is on the subscriber and he is the weak party through the company’s use of its economic strength, In the presence of this condition, the company obtains a very large advantages, whether monetary or non-monetary advantages at the expense of the opposing party, which is the weak party, but the Internet subscription contract cannot be adapted to the Adhesion contract in the sense of what is mentioned in the Iraqi civil law, but it can be adapted as a contract with dilute Adhesion, because at the present time there are Several companies in the field of telecommunications, so the company cannot impose many arbitrary conditions on the subscriber or exempt itself from liability, and that leads to the monopoly authority for one company, and also the subscriber has several options before him, so he can hold the contract with a company that provides internet service with better quality and easier conditions so that the rights and obligations are balanced in the contract.